REVIEW OF AVIATION TERMINOLOGY OF TURKISH AND KAZAKH LANGUAGES - З. Шaдкaм; Г.Е. Хaиргaлиевa (Journal of Oriental Studies, 2019)
Term is an essential part of any language. This statement is not an exception for aviation terminology. This article provides an overview of aviation terminology of Turkish and Kazakh languages. The purpose of the research is a comprehensive comparative study of aviation terms and the identification of features and problems of the translation of aviation terminology into Turkish and Kazakh languages. The relevance of this study lies in the fact that the terms, despite their uniqueness and independence from the context, will be influenced by various linguistic processes, and the translator is challenged with the task of taking into account these features of terms. When writing this article, general scientific and linguistic methods were applied: 1) the method of continuous sampling; 2) conducting a comparative analysis of terms and term combinations of a special vocabulary; 3) scientific description method Key words: term, aviation terminology, term system.